A modelling study on milk lactose hydrolysis and β-galactosidase stability under sonication - Sener, Neslihan; Apar, Dilek Kilic; Ozbek, Belma (ELSEVIER SCI LTD, 2006)
In the present study, it was aimed to investigate the effect of ultrasonication as an alternative method on the kinetics of lactose hydrolysis process. The effects of the duty cycle and acoustic power of sonifier and enzyme concentration on hydrolysis of lactose and as well as on enzyme stability were studied. The lactose hydrolysis reactions were carried out using a commercial beta-galactosidase produced from Kluyveromyces marxianus. Ultrasonic treatment resulted by the lactose hydrolysis degree of 90% and the residual enzyme activity of 75% at the optimum operational conditions; acoustic power of 20 W, duty cycle rate of 10% and enzyme concentration of 1 mL/L. These results show that the sonication was beneficial for lactose hydrolysis in milk. Mathematical models were also derived for residual lactose concentration and residual enzyme activity depending on the operating conditions. The predicted models have been confirmed with the experimental results. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: lactose hydrolysis; milk; beta-galactosidase; sonifier; acoustic power; duty cycle; enzyme concentration; modelling; ESCHERICHIA-COLI; FLOW REACTOR; SKIM MILK; ULTRASOUND; FRAGILIS; KINETICS; STARCH; Biochemistry & Molecular Biology; Biotechnology & Applied Microbiology; Engineering